Selected micronutrient intake and the risk of colorectal cancer. - Ferraroni, M. (Nature Publishing Group, 1994)
The relationship between estimated intake of selected micronutrients and the risk of colorectal cancer was analysed using data from a case-control study conducted in northern Italy. The study was based on 828 patients with colon cancer, 498 with rectal cancer and 2,024 controls in hospital for acute, non-neoplastic, non-digestive tract diseases. Relative risks (RRs) of intake quintiles were computed after allowance for age, sex and other major potential confounding factors, including an estimate of total energy intake. No apparent trend in risk across intake quintiles was evident for retinol, vitamin D, methionine and calcium. For beta-carotene, ascorbic acid, vitamin E and folate there was a trend of a protective effect with increasing consumption: the RR for the highest versus the lowest quintile was 0.32 for beta-carotene, 0.40 for ascorbic acid, 0.60 for vitamin E and 0.52 for folate. These inverse associations were similar for colon and rectal cancer, and consistent across strata of sex and age. When simultaneous allowance was made for all these micronutrients, besides other covariates, the only persistent protective effects were for beta-carotene (RR = 0.38 for the highest quintile) and ascorbic acid (RR = 0.52). Whether this reflects a specific, or stronger, effect of these micronutrients, rather than problems of collinearity between micronutrients or other limitations of the data, remains open to discussion. Still, this study suggests that specific micronutrients may exert an independent protective effect against colorectal carcinogenesis.